2008
DOI: 10.1002/app.29116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silicon carbide filler on mechanical and dielectric properties of glass fabric reinforced epoxy composites

Abstract: Fiber-reinforced polymeric composites (FRPCs) have emerged as an important material for automotive, aerospace, and other engineering applications because of their light weight, design flexibility, ease of manufacturing, and improved mechanical performance. In this study, glass-epoxy (G-E) and silicon carbide filled glass-epoxy (SiC-G-E) composite systems have been fabricated using hand lay-up technique. The mechanical properties such as tensile strength, tensile modulus, elongation at break, flexural strength,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Composite materials have been considered as substitutes for metallic materials, owing to their conformability and high specific mechanical properties. Composites have been used in a variety of applications in aerospace, automotive and construction industries owing to their low density and custom-engineered mechanical, thermal and acoustic properties [1,2]. Epoxy polymer is one of the most used thermosetting materials owing to its easy processing and fabrication, simple tooling and excellent adhesive and optically transparent properties [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite materials have been considered as substitutes for metallic materials, owing to their conformability and high specific mechanical properties. Composites have been used in a variety of applications in aerospace, automotive and construction industries owing to their low density and custom-engineered mechanical, thermal and acoustic properties [1,2]. Epoxy polymer is one of the most used thermosetting materials owing to its easy processing and fabrication, simple tooling and excellent adhesive and optically transparent properties [3].…”
Section: Introductionmentioning
confidence: 99%
“…Particle inclusions can act as barriers against crack propagation and also enhance compressive modulus and strength of the matrix [6]. Particle size and weight fraction for matrix reinforcement are therefore selected to provide higher specific properties for the composite material [2]. Garg and Mai [7] extensively reviewed the toughening mechanisms of micro fillers in epoxy polymers.…”
Section: Introductionmentioning
confidence: 99%
“…B. BEN DIFALLAH 1,2,3 , M. KHARRAT 1, 4* , M. DAMMAK 1,4 and G. improves its abrasive wear and sliding performance with a content of MoS 2 for minimum wear rate around 10 wt%. They also reported that, under sliding conditions, the main wear mechanism of HMW-HDPE was changed from severe melting wear to mild adhesive wear.…”
Section: Disulphide Particlesmentioning
confidence: 99%
“…The dynamic flexu ral loadings in aircraft fuselage must be cons idered in th e structu ral d es ign . In th is case, the composites must provide high stiffness and fatigueresistance [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…. % × − = weight cond weight recond weight cond (6) Recond. weight: mass of sample reconditioned in water after removal of there.…”
mentioning
confidence: 99%